Kepribadian Dalam Perspektif Hamka - Subhi, Muhamad Rifai (Jurnal Fokus Konseling, 2018)
Hamka is a scholar and intellectual who mastered various fields of science, including tasawuf, education, literature, culture, tafsir, jurisprudence, journalism, politics, and so forth. This expertise is what makes researchers to examine his thoughts in terms of each experts expertise. It is also the background of researchers to consider the thought Hamka reviewed through psychology and counseling. His thinking is about the personality who is reflected from his various works. This study uses literature review approach to review Hamka thinking about personality, so that analysis technique used content analysis. Sources of data used are scientific works written directly by Hamka discussing about the personality, and supported by other relevant works. Hamkas thoughts about personality are explained through four things that she thinks to have a major effect on ones personality. Four things are things that can cause personality, things that can strengthen the personality, things that can weaken the personality, and things that can improve the personality.Keywords: Hamka, Personality, Psychology and Counseling